Dual solutions for boundary layer flow of moving fluid over a moving surface with power-law surface temperature - Mukhopadhyay, Swati; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
An analysis of heat transfer for boundary layer forced convective flow past a moving flat surface parallel to a moving stream is presented. The power-law surface temperature at the boundary is prescribed. The surface temperature varying directly (or inversely) with power-law exponent is considered. The similarity solutions for the problem are obtained and the reduced ordinary differential equations are solved numerically. To support the validity of the numerical results, a comparison is made with known results from the open literature for some particular cases of the present study. When the surface and the fluid move in the opposite directions, dual solutions exist.
Keywords: forced convective flow; moving fluid; flat surface; power-law surface temperature; dual solutions